Vitis vinifera L. Leaf Extract, a Microbiota Green Ally against Infectious and Inflammatory Skin and Scalp Diseases: An In-Depth Update - Marta Armari; Elisa Zavattaro; Cesar Francisco Trejo; Alice Galeazzi; Alessia Grossetti; Federica Veronese; Paola Savoia; Barbara Azzimonti (MDPI AG, 2024)
The skin microbiota, with its millions of bacteria, fungi, and viruses, plays a key role in balancing the health of the skin and scalp. Its continuous exposure to potentially harmful stressors can lead to abnormalities such as local dysbiosis, altered barrier function, pathobiont overabundance, and infections often sustained by multidrug-resistant bacteria. These factors contribute to skin impairment, deregulation of immune response, and chronic inflammation, with local and systemic consequences. In this scenario, according to the needs of the bio-circular-green economy model, novel harmless strategies, both for regulating the diverse epidermal infectious and inflammatory processes and for preserving or restoring the host skin eubiosis and barrier selectivity, are requested. Vitis vinifera L. leaves and their derived extracts are rich in plant secondary metabolites, such as polyphenols, with antioxidant, anti-inflammatory, antimicrobial, and immunomodulatory properties that can be further exploited through microbe-driven fermentation processes. On this premise, this literature review aims to provide an informative summary of the most updated evidence on their interactions with skin commensals and pathogens and on their ability to manage inflammatory conditions and restore microbial biodiversity. The emerging research showcases the potential novel beneficial ingredients for addressing various skincare concerns and advancing the cosmeceutics field as well.